2019
DOI: 10.1515/polyeng-2019-0159
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to correlate the physical properties of fossil and subfossil resins with their age and geographic location

Abstract: Abstract Testing of the correlation between physical properties of natural resins such as microhardness, density and UV-excited fluorescence emission with their age, geological conditions, botanical and geographical origin and chemical structure was performed. These physical parameters, especially microhardness, are the result of resins fossilization processes like cross-linking and polymerizations of compounds present in the fossils. In addition, hardening of the resins may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
2
7
2
Order By: Relevance
“…The resins have strong uorescence from green-blue to blue in UVL (365 nm). Their uorescence intensity is higher than those observed for fossil resins from La Cumbre deposit 10,57 .…”
Section: Resultscontrasting
confidence: 60%
“…The resins have strong uorescence from green-blue to blue in UVL (365 nm). Their uorescence intensity is higher than those observed for fossil resins from La Cumbre deposit 10,57 .…”
Section: Resultscontrasting
confidence: 60%
“…Poinar [12] considered that the existence of copal in Madagascar dated from between 3 and 4 Ma ago, while Le Gall et al [81] assigned an age of between 1 and 2.6 Ma, in both cases without evidence. Other authors [13,29,[82][83][84], suggested that "Madagascar copal" from the north coast (Antsiranana) had a presumed age of between 10,000 and 50,000 years; in no case was the exact provenance of the analysed pieces indicated.…”
Section: "Madagascar Copal" Geographical Origin and Agementioning
confidence: 99%
“…resin can harden within days due to the position of the carboxylic group in iso-ozic acid at the C4 position and the enantio configuration 73 giving the impression of being older than it actually is 8 , 15 . Recently, Stach et al 74 attempted to correlate microhardness of copal and amber with age; unluckily, these authors used uncorroborated and wrongly cited ages for the copals tested, apart from the fact that the provenance of Malagasy and Tanzanian copals is frequently uncertain 8 . With this information, they argued an older age for Malagasy copal than that for the Colombian and Tanzanian copals.…”
Section: Discussionmentioning
confidence: 99%